2001
DOI: 10.1139/x00-150
|View full text |Cite
|
Sign up to set email alerts
|

Responses of quaking aspen (Populus tremuloides) seedlings to solution calcium

Abstract: Quaking aspen (Populus tremuloides Michx.) seedlings were grown in nutrient solutions to investigate their responses to a range of solution Ca levels (10-1000 µM) similar to those found in aspen stands of upper Lakes States. Growth increased significantly with increasing level of solution Ca. The level of solution Ca associated with 90% of maximum elongation (critical level) was 61 µM for shoots and 88 µM for roots. Critical Ca levels for biomass probably were lower. Concentrations of Ca in leaves and roots in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
3
20
0
1
Order By: Relevance
“…pH values of the forest floor and mineral soil suggest that trembling aspen stands have a higher productivity in less acid soils (Chen et al 1998). Our findings agree with other studies indicating the optimal soil pH for poplar and aspen to be 5.0-6.5 (Lu and Sucoff 2001;Stanturf et al 2001). The negative correlation between soil pH and tree growth in the current study might not be a direct influence, since the more vigorous aspen growth was observed in the southern part of Estonia, where sandy soils have developed from Devonian sandstone rocks (Fig.…”
Section: Nutritional Status Of 7-yr-old Hybrid Aspenssupporting
confidence: 90%
“…pH values of the forest floor and mineral soil suggest that trembling aspen stands have a higher productivity in less acid soils (Chen et al 1998). Our findings agree with other studies indicating the optimal soil pH for poplar and aspen to be 5.0-6.5 (Lu and Sucoff 2001;Stanturf et al 2001). The negative correlation between soil pH and tree growth in the current study might not be a direct influence, since the more vigorous aspen growth was observed in the southern part of Estonia, where sandy soils have developed from Devonian sandstone rocks (Fig.…”
Section: Nutritional Status Of 7-yr-old Hybrid Aspenssupporting
confidence: 90%
“…Poplars prefer soil pH levels of 6.0Á6.5, but they grow well between 5.5 and 7.5 (Ericsson & Lindsjö, 1981;Lu & Sucoff, 2001;Stanturf et al, 2001). Generally, the same preferences were confirmed in young hybrid aspen plantations on abandoned agricultural lands (Tullus, 2008;Tullus et al, 2007Tullus et al, , 2010b.…”
Section: Hybrid Aspen Review 13mentioning
confidence: 99%
“…Acid deposition can negatively affect trees by increasing the solubility of toxic Al ions, by increasing leaching of base cations, especially Ca and magnesium (Mg) [1,3,[10][11][12] and by lowering pH to toxic levels. [13] Intensive harvesting may also lead to soil acidification and Ca deficiency by removing base cations from the site in tree logs and tops and by accelerating leaching of cations. [10,[14][15][16][17] Previous research in both agronomic crops [18][19][20][21][22][23] and tree species [2,10,[24][25][26][27] has documented that growth is reduced more by a combination of low Ca and high Al than by either factor alone.…”
Section: Introductionmentioning
confidence: 99%